Slow Firing Single Units Are Essential for Optimal Decoding of Silent Speech - Ganesh, Ananya; Cervantes, Andre J.; Kennedy, Philip R. (Frontiers in Human Neuroscience, 2022)
The motivation of someone who is locked-in, that is, paralyzed and mute, is to find relief for their loss of function. The data presented in this report is part of an attempt to restore one of those lost functions, namely, speech. An essential feature of the development of a speech prosthetic is optimal decoding of patterns of recorded neural signals during silent or covert speech, that is, speaking ‘inside the head’ with no audible output due to the paralysis of the articulators. The aim of this paper is to illustrate the importance of both fast and slow single unit firings recorded from an individual with locked-in syndrome and from an intact participant speaking silently. Long duration electrodes were implanted in the motor speech cortex for up to 13 years in the locked-in participant. The data herein provide evidence that slow firing single units are essential for optimal decoding accuracy. Additional evidence indicates that slow firing single units can be conditioned in the locked-in participant five years after implantation, further supporting their role in decoding.